Why shamanism? Why Peru? Why now? : why are Westerners travelling to Peru for a shamanic experience? : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Social Anthropology at Massey University - Maw, Nicola (Massey University, 2002)
Why Shamanism? Why Peru? Why Now? This thesis answers these questions by exploring the richness of the Peruvian Amazon, Andean mountains, and the shamanic traditions that dwell within. I describe why it is that members of the West turn towards shamanism and specifically Peruvian shamanism for spiritual, environmental and medical reasons. The phenomenon of the shamanic tour is explored and the scientists who study Peruvian shamanism in order to understand and transfer its benefits to the Western world are also considered. Reasons for their interest include: curiosity, spiritual enlightenment, drug tourism, medical (psychological and physiological) and the need to experience and record shamanic knowledge before it is lost. Reasons why this knowledge is sought and made available at this time is explained including reference to the new age movement, disillusionment with religious and biomedical institutions in the West, changing worldviews and the Q'ero Inkan prophecy which foretells the time when the eagle of the North (the Western world) and the condor of the South (traditional world) will fly together and the Earth will awaken. As Western interest increases, and as the world changes, intellectual property rights become an issue for these traditional societies. Indigenous knowledge and current trends and implications of international intellectual property legislation are discussed.
Keywords: Spiritual life; Peru; Shamanism; Tourism